Plants of genus Mentha: From farm to food factory
Genus Mentha, a member of Lamiaceae family, encompasses a series of species used on an industrial scale and with a well-described and developed culture process. Extracts of this genus are traditionally used as foods and are highly valued due to the presence of significant amounts of antioxidant phenolic compounds. Many essential oil chemotypes show distinct aromatic flavor conferred by different terpene proportions. Mint extracts and their derived essential oils exert notable effects against a broad spectrum of bacteria, fungi or yeasts, tested both in vitro or in various food matrices. Their chemical compositions are well-known, which suggest and even prompt their safe use. In this review, genus Mentha plant cultivation, phytochemical analysis and even antimicrobial activity are carefully described. Also, in consideration of its natural origin, antioxidant and antimicrobial properties, a special emphasis was given to mint-derived products as an interesting alternative to artificial preservatives towards establishing a wide range of applications for shelf-life extension of food ingredients and even foodstuffs. Mentha cultivation techniques markedly influence its phytochemical composition. Both extracts and essential oils display a broad spectrum of activity, closely related to its phytochemical composition. Therefore, industrial implementation of genus Mentha depends on its efficacy, safety and neutral taste.